2024
DOI: 10.1021/acsestair.3c00081
|View full text |Cite
|
Sign up to set email alerts
|

Passive Air Sampling Networks Combined with Multivariate Statistics Reveal Widespread Non-Aroclor Polychlorinated Biphenyl Sources to the Canadian Atmosphere

Jenny Oh,
Chubashini Shunthirasingham,
Faqiang Zhan
et al.

Abstract: Polychlorinated biphenyls (PCBs) in the North American atmosphere were originally thought to arise through volatilization of commercial Aroclor mixtures, but there is growing evidence of atmospheric emissions of non-Aroclor, i.e., unintentionally produced, PCBs. Here, we report on measurements of all 209 PCB congeners in 169 passive air samples collected between 2019 and 2022 using networks established around the Salish Sea, British Columbia (BC), and along the St. Lawrence River and Estuary, Quebec (QC), in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…The unintentional production of several different PCB congeners from the use of 2,4-dichlorobenzoyl peroxide as an initiator in silicone and polyester production has been known since the early 1990s . Twenty-five years later, studies revealed that the use of this chemical continues to be a notable and widespread source of emissions of PCBs to the indoor and outdoor atmosphere. , Many other sources of unintentionally produced PCBs have been identified. Because most monitoring efforts do not quantify the relevant congeners, no knowledge of temporal trends in their release rates currently exists …”
Section: Apparent Complacency In Response To Increasing Releases Of U...mentioning
confidence: 99%
“…The unintentional production of several different PCB congeners from the use of 2,4-dichlorobenzoyl peroxide as an initiator in silicone and polyester production has been known since the early 1990s . Twenty-five years later, studies revealed that the use of this chemical continues to be a notable and widespread source of emissions of PCBs to the indoor and outdoor atmosphere. , Many other sources of unintentionally produced PCBs have been identified. Because most monitoring efforts do not quantify the relevant congeners, no knowledge of temporal trends in their release rates currently exists …”
Section: Apparent Complacency In Response To Increasing Releases Of U...mentioning
confidence: 99%